Integration concepts for multi-organ chips: how to maintain flexibility?! - Rogal, Julia (Future Sci OA, 2017)
Multi-organ platforms have an enormous potential to lead to a paradigm shift in a multitude of research domains including drug development, toxicological screening, personalized medicine as well as disease modeling. Integrating multiple organ–tissues into one microfluidic circulation merges the advantages of cell lines (human genetic background) and animal models (complex physiology) and enables the creation of more in vivo-like in vitro models. In recent years, a variety of design concepts for multi-organ platforms have been introduced, categorizable into static, semistatic and flexible systems. The most promising approach seems to be flexible interconnection of single-organ platforms to application-specific multi-organ systems. This perspective elucidates the concept of ‘mix-and-match’ toolboxes and discusses the numerous advantages compared with static/semistatic platforms as well as remaining challenges.